2018
DOI: 10.1111/jace.15912
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of Eu atoms in AlN lattice and the first‐principles simulations

Abstract: Rare-earth metal (Eu)-doped aluminum nitride has potential application as luminescence materials due to its unusual mechanical and physical properties, as well as high chemical stability. Here, we investigate the energetics, local structure and optical and electronic properties by means of a combination of experimental observations (XDR, SEM, HR-TEM and XANES) and first-principles simulations. Present study has revealed that Eu ions are likely to be co-doped with O in the form of Eu-O pairs. Eu ions or Eu-O pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Further increase in concentration of Dy 3+ ( x > 0.05) induced a decrease in photoluminescence emission intensity. The observed decrease in photoluminescence intensity is associated to phenomenon of concentration quenching occurred as a result of the non‐radiative energy transfer between the closest Dy 3+ dopants 4,56,57 . More specifically, since the concentration of Dy 3+ ions in the host lattice of Ca 2 LuTaO 6 double perovskite oxide phosphors increase, the gap between two adjacent Dy 3+ ions decreased, leading to an increase in energy migration that favoure the possibility of non‐radiative transitions occurring 43‐46,58 …”
Section: Resultsmentioning
confidence: 98%
“…Further increase in concentration of Dy 3+ ( x > 0.05) induced a decrease in photoluminescence emission intensity. The observed decrease in photoluminescence intensity is associated to phenomenon of concentration quenching occurred as a result of the non‐radiative energy transfer between the closest Dy 3+ dopants 4,56,57 . More specifically, since the concentration of Dy 3+ ions in the host lattice of Ca 2 LuTaO 6 double perovskite oxide phosphors increase, the gap between two adjacent Dy 3+ ions decreased, leading to an increase in energy migration that favoure the possibility of non‐radiative transitions occurring 43‐46,58 …”
Section: Resultsmentioning
confidence: 98%
“…reported that the entry of Eu 2+ into the AlN lattice distorted the AlN lattice. Yin et al 31 . prepared AlN:Eu 2+ phosphor by gas reduction nitridation method and investigated the doping sites of Eu ions in AlN samples.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, Yin et al 30 reported that the entry of Eu 2+ into the AlN lattice distorted the AlN lattice. Yin et al 31 prepared AlN:Eu 2+ phosphor by gas reduction nitridation method and investigated the doping sites of Eu ions in AlN samples. Their findings indicated that even dopant atoms with extremely large size mismatch could be incorporated into host crystal lattice through Eu substitution Al at or near the surface.…”
Section: Effects Of Mn 2+ Concentrationmentioning
confidence: 99%
“…As observed, the cell volume expands with the increase of Eu 2+ doping concentration, which can be ascribed to the substitution of Al by Eu. Yin et al have reported that the single Eu dopant tended to replace the Al site in edge of the AlN crystallites via direct viewing in the atomic scale. Because the radius of Eu 2+ is larger than that of Al 3+ , the doping of Eu 2+ can cause the distortion of the AlN lattice, leading to the cell volume expansion.…”
Section: Resultsmentioning
confidence: 99%
“…As observed, the cell volume expands with the increase of Eu 2+ doping concentration, which can be ascribed to the substitution of Al by Eu. Yin et al 28 have reported that the single Eu dopant tended to replace the Al site in edge of the AlN crystallites via direct viewing in the atomic scale. Because the radius of Eu 2+ is larger than that of Al 3+ , 29 30 With the increase of Eu 2+ concentration, the intensity of AlN absorption band significantly decrease, and the main peaks shift to a low energy centered at about 700 cm −1 , suggesting the change of Al-N force constant due to the Eu 2+ dissolution into the AlN lattice.…”
Section: Effects Of Caf 2 Additivesmentioning
confidence: 99%